(untitled) (Research, Society and Development, 2024)
This study aims to analyze research conducted between 2013 and 2023 on the teaching of rational numbers, with the aim of identifying elements that can drive learning in this mathematical domain. The research seeks to deepen understanding of the topic, map current researchers’ interests, and find indicators that can guide the incorporation of innovative technologies and resources into mathematics education. To achieve this goal, a literature review was conducted, selecting articles from various sources, including Google Scholar, PubMed, and Scielo. The analysis of the studies aims not only to provide insights into the current state of research in this field but also to inspire teachers with contextualized approaches and strategies, promoting reflections on pedagogical practices related to the teaching and learning of rational numbers. By considering the main findings and conclusions of these studies, it is hoped to provide readers with a comprehensive and updated overview of the trends and challenges faced in the teaching of rational numbers.